Preliminary Studies on some Nepalese Kitchen Spices for their Antibacterial Activities - Khanal, Dhama Prasad; Raut, Bechan; Bajracharya, Kiran Sundar; Karki, Raj Kumar (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9903 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 12-18